Counseling and oral splint for conservative treatment of temporomandibular dysfunction: preliminary study - Ana Paula Varela Brown MARTINS; Luana Maria Martins de AQUINO; Carolina Beraldo MELOTO; Célia Marisa Rizzatti BARBOSA
Abstract Introduction Temporoamndiular Disorders (TMD) involve the masticatory muscles, temporomandibular joint (TMJ) or both. The most common symptom is pain, which is usually located in the muscles of mastication, pre-auricular region, and / or ATM, especially during mandibular function. The main treatment for TMD is related to pain relief. Objective The purpose of this case report was to evaluate the reduction of pain symptoms using Visual Analogue Scale (VAS) of patients with TMD treated with counseling and use of occlusal splint (OS). Material and method 16 subjects had participated in this study, that was composed by 4 appointment with 7-day interval between each (CEP FOP / Unicamp - 137/2009). In the first, an examiner used the Research Diagnostic Criteria for Temporomandibular Disorders (RDC / TMD) to diagnose each patient and delivered a VAS to register the intensity of daily pain. In the second, counseling, molding of both dental arcs to fabricate the OS and the delivery of new VAS were performed. In the third, there was the installation and adjustment of the OS and the delivery of another scale, and in the last, possible adjustments on the OS were done. Data were analyzed by ANOVA two way and Tukey post-test at 5% significance level. Result There was significant difference when comparing the intensity of pain of individuals after installation of splint with the baseline data and after counseling (p = 0.05). Conclusion According to the result of this study, the treatment of TMD associating counseling occlusal splint is effective in reducing pain intensity.